Koncepcje ladu stanowionego i spontanicznego a analizy procesow transformacji systemowej - przyklad bylej NRD w latach 1990-2010 - Michal Moszynski (Institute of Economic Research (IER), 2011)
– The study attempts to develop the concept of using the idea of constructed and spontaneous economic order in the analysis of system transformation process of the former German Democratic Republic. The paper consists of six parts and ends with conclusions. In the first introductory part, an overview of economic theories used by researchers in the analysis of economic transformation is outlined, it is pointed out that one of them is ordoliberalism. The second part introduces the concepts of constructed and spontaneous economic order formulated by W. Eucken and F.A. von Hayek. It provides an introduction to the next point, which is trying to demonstrate that these broad categories of thought are a good basis for the conduct of discussion about the process of economic transformation. Next the interest is focused on the problem of actuality of ordoliberal ideas arisen several decades before the system changes in the countries of Central and Eastern Europe and its usefulness for analyzing these phenomena. The fifth part of the paper contains a proposal for a research approach for operationalisation of broad and abstract concept of constructed and spontaneous economic order. Specificity of the transformation of the former GDR - in very general terms - is the subject of out in the last part of the paper.
Keywords: B52; N14; P20; P30; 330; institutional economics; effectiveness of institutional system; TOPSIS method; global knowledge-based economy; European Union